Ouidah The Social History of a West African Slaving Port 1727-1892. - Law, Robin (Western African studies., 2004)
Ouidah, an African town in Dahomey, now Benin, was the principal pre-colonial commercial centre of its region and this is the first detailed study of the town's history and its role in the Atlantic slave trade.